Application of Metacognitive Knowledge-Based Learning On Students Learning Outcomes in Heredity Material at Grade IX Junior High School of SMP Negeri 1 Talaga Jaya - Anuz, Fadria; Nusantari, Elya; Abdul, Aryati; Yusuf, Frida Maryati; Mamu, Hartono; Aydalina, Regina Valentina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
This study aims to the determine the application of metacognitive knowledge-based learning on students’ learning outcomes in heredity material grade IXth at Junior High School of SMP Negeri 1 Talaga Jaya. This study employs a quantitative descriptive approach, utilizing a pre-experimental design that includes a single group pretest and posttest design. The subjects consist of grade IXth-group 1 during the odd semester of the 2022/2023 academic year, comprising a total of 30 students. The instruments used in this study consisted of questions based on metacognitive knowledge, lesson plans students’ worksheet, teacher activity sheet, and student activity sheet. The research data are analyzed using the formula of teacher ativity, student activity, individual completeness, pretest and posttest average scores, and students’ N-gain. The result showed that the scores of students’ learning outcomes increased, as observable from the posttest scores, which were higher than the pretest scores. The pretest score obtained at the first meeting was 28.53 and the posttest was 75.07. In the second meeting the pretest score was 21.27 and the posttest was 77.00 for the third meeting the pretest score was 27.00 and the posttest was 78,06. In addition, the N-gain score of students at the first meeting was 0.65 or in the medium category, in the second meeting was 0.71 an in the third meeting was 0.71 or in the high categories